Development of Interactive Multimedia to Foster Students' Information Literacy Ability on Salt Hydrolysis Topic - Dewi Yuliatin; Citra Ayu Dewi; Khaeruman Khaeruman; Suryati Suryati; Yeti Kurniasih (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to produce and determine the feasibility of interactive multimedia salt hydrolysis to grow students' information literacy skills. This research is a development research which includes 10 stages of implementation, namely potential and problems, collecting information, product design, design validation, design revision, product trial, product revision, usage trial, product revision, and bulk product. However, this study only reached the stage of product revision. The interactive multimedia produced was then validated by 2 expert lecturers in the field of chemistry education, and for practitioner tests by 1 chemistry teacher and then a limited group trial was carried out involving 15 students of SMA Negeri 1 Batulayar. Based on the assessment of two lecturers as validators getting an average of 91,2% with a very decent category, the practitioner test results got a percentage of 94.3% with a very decent category, and the results of a limited group trial by 15 students got an average percentage of assessments for ease, readability, display, material, and motivation of 88.6% with good categories. So it can be concluded that the product of interactive multimedia development of salt hydrolysis has met the feasibility aspect and this medium can be used in learning on salt hydrolysis material.